MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE KELAS VII-C DENGAN KOMPETENSI DASAR MENGIDENTIFIKASI TINDAKAN EKONOMI BERDASARKAN MOTIF DAN PRINSIP EKONOMI DALAM BERBAGAI KEGIATAN SEHARI-HA - Widari Pramudiati; Siti Seituni (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
: Researcher chooses Research execution at SMP Negeri 1 Panarukan because study IPS that walk at SMP Negeri 1 Panarukan in this time still centrally in teacher. In word square student in one certain class is divided to be group with member 4-5 person and every group must heterogeneous that consists of man and woman. Team member uses activity sheet or other study ware to successful study the lesson matter, and then mutual help in do discussion. based on background on, so problem formulation as follows: 1) is enhanced result learns to pass type co-operative study model applications word square class VII-C with competence base identify economy action based on motive and economic principle in so many activity everyday subject IPS at SMP Negeri 1 Panarukan school?, 2) is enhanced activity learns to pass type co-operative study model applications word square class VII-C with competence base identify economy action based on motive and economic principle in so many activity everyday subject IPS at SMP Negeri 1 Panarukan school?. Research design in this Research CAR through collaboration teacher that appointed 2 cycles.in CAR there 4 stages that is planning, action, observation and reflection. primary data by using repetition test and observation with at checklist, and secondary data with interview. Researcher uses target value necessities determine successful criteria to analyzes data. Based on Research result at chapter iv inferential as follows: 1) there result enhanced learns to achieve ketuntasan 90% pass type co-operative study model applications word square class VII-C with competence base identify economy action based on motive and economic principle in so many activity everyday subject IPS at SMP Negeri 1 Panarukan school,2) there activity enhanced learns as big as 83% pass type co-operative study model applications word square class VII-C with competence base identify economy action based on motive and economic principle in so many activity everyday subject IPS at SMP Negeri 1 Panarukan school.